Organizational Leadership Mediates Organizational Culture and Commitment to Employee Performance at BPR Banks in Banyumas Regency - Agus Setiono; Najmudin, Najmudin; Sudarto, Sudarto (Cita konsultindo, 2024)
Organizational leadership plays a vital role in determining the direction and success of a company. In the banking context, especially at Rural Credit Banks (BPR) in Banyumas Regency, the aim of this research is to analyze and understand the role of organizational leadership as a mediator in the relationship between organizational culture and employee commitment to their performance at Rural Credit Banks (BPR) in Banyumas Regency. This research was conducted at BPR Banks in Banyumas Regency by giving questionnaires to bank leaders using Google Form. In this study the entire population was used as the research sample. The reason is, there are only 67 BPR banks in Banyumas Regency and the analysis tool is SEM PLS. The results of this research are that organizational culture has a proven influence on organizational leadership, this is because the P-Value value of 0.002 is smaller than the alpha value of 0.05, commitment has a proven effect on organizational leadership, this is because the P-Value value of 0.001 is smaller than The alpha value is 0.05 and organizational leadership has a proven effect on employee performance, this is because the P-Value value of 0.000 is smaller than the alpha value of 0.05